Sustainability Strategy in Constrained Economic Times. Issue 2 (April 2015) - Barnett, Michael L.; Darnall, Nicole; Husted, Bryan W.
Abstract : While firms have increasingly adopted environmentally and socially sustainable management strategies, little is known about how these organizations react during times of economic constraint. On the one hand, conventional wisdom suggests that firms' sustainability strategy would be de-emphasized. However, emerging scholarship suggests that many firms may increase their sustainability investments during constrained economic times. Building on the articles comprising this Special Issue, we offer notable evidence that firms tend to shift their sustainability strategy in innovative ways that enable them to do more with less and increase firm value without undertaking significant cutbacks. Specifically, we argue that, during times of economic constraint, firms a) engage in sustainability "trimming" to adapt to their new economic setting; b) use trimming to compete more effectively; and c) trim in ways that are path dependent, building upon prior complementary capabilities and resources. We formulate an explanation for these novel findings and conclude with observations about future research opportunities.